Post-industrial Technological Mode of Production: Theory, Economic and Environmental Features, Discussion Questions - Rumyantsev, Aleksey Aleksandrovich (International Journal of Economics and Financial Issues, 2015)
The article explores the emergence of a new stage of technological development - the post-industrial technological mode of production. Based on content analysis of industrial technologies and technologies of the new wave there is proposed criterion which can differ postindustrial technological mode of production from industrial. It is shown that a new wave of technologies: renewable energy, nanotechnology, biotechnology, information and communication technologies - build the core of the post-industrial technological mode of production. Being at the beginning of its formation, it can only be desÑribed by some economic and environmental features. Attention is drawn to the success of post-industrial technologies in ecology and their possible adverse effects on the environment and human, the need for their thorough investigation. There are given the facts of the development of post-industrial business technologies, the formation of a new structure of energy and production. It is proved that there is no reason to consider contemporary social problems as problems of post-industrial society, they are peculiar to the modern super industrial society. Keywords: Post-industrial technological mode of production, economy, ecology, social expectation JEL Classifications: L52, O33, P48